2017
DOI: 10.1016/j.jpainsymman.2016.12.339
|View full text |Cite
|
Sign up to set email alerts
|

Common and Distinct Characteristics Associated With Trajectories of Morning and Evening Energy in Oncology Patients Receiving Chemotherapy

Abstract: Context While energy conservation strategies are recommended in clinical practice guidelines, little is known about changes in energy levels in oncology patients undergoing cancer treatment. Objectives To identify variations in the trajectories of morning and evening energy levels and to determine which characteristics predicted initial levels as well as the trajectories of morning and evening energy. Methods Outpatients receiving chemotherapy (CTX) completed demographic and symptom questionnaires six time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…This finding highlights the importance of assessing for diurnal variations in fatigue severity (61) as well as decrements in energy (62, 63). In addition, research from our group demonstrated distinct characteristics associated with the trajectories of morning and evening fatigue and energy in patients with cancer (15, 45, 64, 65), supporting the need for comprehensive assessment of fatigue both in research and clinical care. Furthermore, management strategies for cancer-related fatigue, such as energy conservation and exercise (66, 67), may impact morning and evening fatigue differently.…”
Section: Discussionmentioning
confidence: 53%
“…This finding highlights the importance of assessing for diurnal variations in fatigue severity (61) as well as decrements in energy (62, 63). In addition, research from our group demonstrated distinct characteristics associated with the trajectories of morning and evening fatigue and energy in patients with cancer (15, 45, 64, 65), supporting the need for comprehensive assessment of fatigue both in research and clinical care. Furthermore, management strategies for cancer-related fatigue, such as energy conservation and exercise (66, 67), may impact morning and evening fatigue differently.…”
Section: Discussionmentioning
confidence: 53%
“…Previous work from our research team demonstrated that although morning and evening fatigue as well as morning and evening energy are associated with depression, they are distinct symptoms. 74 , 75 , 76 Although cancer-related cognitive impairment occurs in 75% of oncology patients, 34 91.5% of the patients in the stressed class reported clinically meaningful decrements in cognitive function. Finally, although fewer patients in the nonstressed group (54.4%) compared with the stressed group (75.9%) reported pain, both groups reported pain severity scores in the moderate-to-severe range that had a moderate impact on their functional activities.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the literature uses the terms energy and fatigue interchangeably, [72,73] a growing body of evidence from our group [74,75] and others [76][77][78] suggests that energy and fatigue are distinct but related symptoms. In our previous report of characteristics associated with inter-individual differences in the trajectories of morning and evening energy, [74] lack of regular exercise (i.e., dichotomous outcome) was associated with significantly lower levels of morning but not evening energy. However, in the current study, our findings suggest that level of exercise influences decrements in both morning and evening energy.…”
Section: Discussionmentioning
confidence: 99%